2017
DOI: 10.1007/s10337-017-3387-y
|View full text |Cite|
|
Sign up to set email alerts
|

CE Separation and ICP-MS Detection of Gold Nanoparticles and Their Protein Conjugates

Abstract: A full understanding and mediation of nanoparticle–serum protein interactions is key to design nanoparticles with vivid functions within the body, and to solve this problem one needs to differentiate and characterize individual nano-protein conjugates. In this paper, the authors applied capillary electrophoresis combined with inductively coupled plasma mass spectrometry detection to study the behavior of gold nanoparticles of different geometry, size and surface functionalization upon interacting with serum pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 44 publications
0
9
0
2
Order By: Relevance
“…Matczuk and co‐workers characterized the protein corona of gold NPs at equilibrium conditions by exposing the NPs to bovine and human serum . This study was later expanded to different particle geometries (rod‐ and spherical‐shaped), size, surface functionalization, applied dose (NP‐to‐protein molar ratio) and exposition time . Subsequently, they investigated the cellular uptake of gold NPs in artificial cytosol (normal and cancer conditions) .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Matczuk and co‐workers characterized the protein corona of gold NPs at equilibrium conditions by exposing the NPs to bovine and human serum . This study was later expanded to different particle geometries (rod‐ and spherical‐shaped), size, surface functionalization, applied dose (NP‐to‐protein molar ratio) and exposition time . Subsequently, they investigated the cellular uptake of gold NPs in artificial cytosol (normal and cancer conditions) .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Here, capillary electrophoresis (CE), which is well known not only as an efficient separation technique but also as a viable tool to study chemical reactions, including kinetic measurements and the analysis of chemical equilibria [16], features several benefits such as high separation efficiency, short analysis time periods, high mass sensitivity, very low chemical and sample consumptions and the characterization of interacting species in a solution [17]. Therefore, CE in the affinity capillary electrophoresis mode (ACE) is a powerful technique for the characterization of NPs and their interaction with other (bio)molecules [18][19][20][21][22][23][24][25]. In ACE, increasing amounts of ligands are simply added to the running buffer, leading to changes in the migration time of the interacting analyte.…”
Section: Introductionmentioning
confidence: 99%
“…They were able to identify conjugates of different Au-nanocarriers with individual proteins by the specific migration time. [56,57] Remarkably,e ven the differ-entiation between AuNC-transferrin conjugates with or without complexed iron ions was possible.B yv arying the incubation time of the AuNCs in human blood serum, they evaluated the dynamic development of the protein corona formation. Their findings showed an increasing amount of albumin on the nanocarrier surface with an increasing incubation time.T hus,C Ep roves to be am ild separation technique,a llowing also reversibly bound proteins to be analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…on gold nanocarriers (AuNCs) showed that CE is a very precise separation method. They were able to identify conjugates of different Au–nanocarriers with individual proteins by the specific migration time . Remarkably, even the differentiation between AuNC–transferrin conjugates with or without complexed iron ions was possible.…”
Section: Separation Of the Nanocarrier–protein Corona Complex From Frmentioning
confidence: 99%